QUALIFICATION WEB-BASED TESTING SYSTEM - Kotyak, В.В. (Journal of Information Technologies in Education (ITE), 2013)
The article defines a set of characteristics for quality web-based systems testing academic achievement relative to the international standard ISO 9126. The analysis platforms TCExam, TAO and OpenTest2.